The Tensions between Ukuthwasa and Labour Laws in South Africa: A Human Rights-Based Approach - Stewart Lee Kugara; Melisa Mutsa Chawaremera (E-Journal of Humanities, Arts and Social Sciences)
This paper appraises the tensions between the cultural practice of ukuthwasa and fundamental human rights in South Africa. This is particularly within the context of modern labour laws and workplace practices. A doctrinal research methodology is employed to analyse the human rights implications of allowing or denying employees the right to engage in the cultural practice of ukuthwasa. This approach enables an analysis and interpretation of relevant legislative provisions, case law and human rights frameworks governing workplace and cultural rights. The study reveals that there are multilayered tensions between the recognition of ukuthwasa and the enforcement of labour laws, which often overlook or conflict with the spiritual and cultural obligations of employees. A critical human rights-based analysis, reveals that the failure to balance cultural rights with workplace obligations can lead to significant human right violations, including unlawful dismissals or infringement of religious and cultural freedoms. This study highlights the need for a more sensitive and inclusive approach to managing cultural practices in corporate environments. Further, this study recommends an approach to addressing cultural rights and fundamental human rights within the workplace environment. Employers should be concientised about the importance of cultural and religious rights, while employees must be aware of their responsibilities within the framework of labour law. Ideally, this will mitigate conflicts or dismissals. This study contributes to the ongoing dialogue on cultural rights and labour law. It also provides insights for employers on managing the delicate balance between cultural practices and legal obligations in the modern workplace.